Overview of the un technology facilitation mechanism for implementation of sustainable development goals - Nguyen Hong Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The Technology Facilitation Mechanism is a new international mechanism of the United Nations, through this mechanism the governments, civil society, business, the scientific community, UN agencies and other actors can collaborate, connect, discuss and evaluate different technologies and at the same time this mechanism can help identify the advantages and disadvantages of implementing the sustainable development goals. The article gives an overview of the United Nations technology facilitation mechanism to achieve the Sustainable Development Goals. On the basis of analyzing the experiences of three countries (Japan, China and India) in the implementation of the technology facilitation mechanism (TFM), the article proposes some suggestions for Vietnam in developing this mechanism in the future.